Turkish As A Heritage Language In Skopje - Behice Varışoğlu; Serdar Başutku (Sakarya University Journal of Education)
Today, one of the countries where Turkish language teaching is common is the Republic of North Macedonia, located in the Balkan peninsula. Many ethnic communities live in North Macedonia. Macedonians, Albanians, Turks, Bosnians, Serbs, Vlachs and Romani constitute the different ethnic national structure of North Macedonia. As in many countries of the Balkans, Turks living in North Macedonia have preserved their mother tongue, culture and traditions. In addition, ethnic groups in North Macedonia were given the right to education in their mother tongue, and thus education and training in Turkish continued. Since Turkish was the language of education, science, art and commerce in this region during the Ottoman period, it has been able to maintain its influence and existence until today. The speakers of Turkish as a heritage language in this region are not only Turks. Other ethnic groups (Romani, Bosnian, Serbian, Vlach, Torbesh, Bulgarian), especially Albanians, are both carriers and protectors of Turkish as a heritage language. In the Balkan geography, where linguistic and cultural heritage is a richness that creates mutual understanding, Skopje is one of the places where individuals from different cultures and ethnic origins come together. The aim of this study is to reveal the socio-cultural role of Turkish in intercultural interaction in Skopje. Today, the existence of Turkish as a heritage language in the Balkans, especially in Skopje, is influenced not only by the Turks in the region, but also by the existence of other ethnic groups. In the study, non-interactive qualitative research design was used. In this study, it is aimed to define the existence of Turkish in Skopje and to evaluate it within the scope of heritage language. In this context, it is thought that the study will contribute to the field by adding new and different dimensions to the concept of heritage language due to the presence of Turkish in the Balkans.